Programy heraldyczne w dekoracji kościołów parafialnych w Kraśniku i Chodlu - Soćko, Adam (Artium Quaestiones, 2018)
The essay is an analysis of coats of arms, mainly from the second quarter of the 16th century, connected with the architecture and decoration of the church of the Regular Canons in Kraśnik and the parish church in Chodel. The identification of numerous coats of arms used to decorate the keystones, supports, portals, balustrades, and facades of the Kraśnik church confirms two stages of its construction by two branches of the Tęczyński family (coat of arms Topór ) in the 15th and 16th centuries. The identification of the coats of arms painted on the chancel vault of the church in Chodel determines the dating of its decorations and commemorates the town’s proprietors – the Maciejowski family and their family connections in the second quarter of the 16th century. The identification of the coats of arms makes it possible to propose precise dating of the construction of both churches.